Multimodal treatment of resectable pancreatic ductal adenocarcinoma. (March 2017) - Silvestris, Nicola; Brunetti, Oronzo; Vasile, Enrico; Cellini, Francesco; Cataldo, Ivana; Pusceddu, Valeria; Cattaneo, Monica; Partelli, Stefano; Scartozzi, Mario; Aprile, Giuseppe; Casadei Gardini, Andrea; Morganti, Alessio Giuseppe; et al.
Abstract: After a timing preoperative staging, treatment of resectable pancreatic adenocarcinoma (PDAC) includes surgery and adjuvant therapies, the former representing the initial therapeutic option and the latter aiming to reduce the incidence of both distant metastases (chemotherapy) and locoregional failures (chemoradiotherapy). Herein, we provide a critical overview on the role of multimodal treatment in PDAC and on new opportunities related to current more active poli-chemotherapy regimens, targeted therapies, and the more recent immunotherapy approaches. Moreover, an analysis of pathological markers and clinical features able to help clinicians in the selection of the best therapeutic strategy will be discussed. Lastly, the role of neoadjuvant treatment of initially resectable disease will be considered mostly in patients whose malignancy shows morphological but not clinical or biological criteria of resectability. Depending on the results of these investigational studies, today a multidisciplinary approach can offer the best address therapy for these patients.